Foreign body ingestion in children and their follow-up in a tertiary care hospital – A prospective study - Jayakumar P; Selvakumar M; Meenakshi Sundari S; Rock Britto D (Asian Journal of Medical Sciences, 2023)
Background: Foreign body (FB) ingestion is a common pediatric surgery emergency, with potential complications such as perforation, obstruction, and bleeding. The demographics, characteristics, and management of these cases can vary based on factors such as age, gender, and type of FB ingested. Aims and Objectives: This study aimed to analyze these factors in a prospective study of children with FB ingestion. Materials and Methods: This was a prospective observational study done under 13 years of age with FB ingestion who presented to a tertiary care hospital over a period of 15 months. Results: A total of 133 cases were included, with a mean age of 6.15 years and a higher prevalence in males (60.2%). The most common age group affected was 5–13 years (50.4%). The mean length of ingested FB was 2.77 cm, with 52.6% of cases ingesting FBs >2 cm. The majority of FBs were blunt (92.5%) and circular in shape (61.7%). The primary reason for ingestion was playing (95.5%). The most common site of FB impaction was the intestine (50.4%). Most cases were managed by observation (93.2%). Conclusion: FB ingestion is a common pediatric emergency, with a higher prevalence in males. Most cases can be managed by observation, and endoscopic removal or PR may be required in a small proportion of cases. Awareness of the risk factors and clinical presentation of FB ingestion can aid in prompt diagnosis and management of these cases.